Happiness, Skillful Actions, and Good Morality - Siu, Ong Cin; (Br. PhápTử), Junaidi; Lamirin, Lamirin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This paper aims to answer the simple question: what is the concept of happiness according to Buddhism? How significant are the skilful actions linked to good morality to produce happiness, and how do the unskilful actions performed by a clouded mind cause unhappiness.Those who are at peace in the present moment might feel a glimpse of happiness just by reading the current sentences. On the other hand, those who are not at ease right now might wish to dispel their uneasiness right away. What are the elements that contribute to our happiness according to Buddhism? Human life aims to find happiness and avoid suffering.Many people in our society and spiritual leaders have laid down many ways to happiness, but nowadays, humans wonder what true happiness is. We want to attain happiness, but many times we behave in the opposite direction. If we can understand the essence of happiness, then the chance to realize it will require little effort.